Increasing the Dimensionality of Soft Microstructures through Injection‐Induced Self‐Folding. Issue 38 (6th August 2018) - Ranzani, Tommaso; Russo, Sheila; Bartlett, Nicholas W.; Wehner, Michael; Wood, Robert J.
Abstract: Devices fabricated using soft materials have been a major research focus of late, capturing the attention of scientists and laypersons alike in a wide range of fields, from microfluidics to robotics. The functionality of such devices relies on their structural and material properties; thus, the fabrication method is of utmost importance. Here, multilayer soft lithography, precision laser micromachining, and folding to establish a new paradigm are combined for creating 3D soft microstructures and devices. Phase‐changing materials are exploited to transform actuators into structural elements, allowing 2D laminates to evolve into a third spatial dimension. To illustrate the capabilities of this new fabrication paradigm, the first "microfluidic origami for reconfigurable pneumatic/hydraulic" device is designed and manufactured: a 12‐layer soft robotic peacock spider with embedded microfluidic circuitry and actuatable features. Abstract : Multilayer soft lithography, precision laser micromachining, and folding are combined to establish a new paradigm for creating 3D soft microstructures and devices. Phase‐changing materials are exploited to transform actuators into structural elements, allowing 2D laminates to evolve into a third spatial dimension. This results in a 12‐layer soft robotic peacock spider with embedded microfluidic circuitry and actuatable features.